Redesigning Juvenile Probation to Align With Behavioral Health and Positive Development Principles: A Quasi-Experimental Study - Cunningham, Kathryn A. (Criminal justice and behavior, 2023)
Science advisory boards and policy organizations have called for adolescent brain science to be incorporated into juvenile probation operations. To achieve this, Opportunity-Based Probation (OBP), a probation model that integrates knowledge of adolescent development and behavior change principles, was developed in collaboration with a local juvenile probation department. The current study compares outcomes (recidivism and probation violations) for youth in the OBP condition versus probation as usual. Inverse probability weighting (IPW) and coarsened exact matching (CEM) were used to estimate causal effects of OBP’s average treatment effect (ATE). Results indicated clear effects of OBP on reducing criminal legal referrals, but no significant effects were observed for probation violations. Overall, results provide promising recidivism-reduction effects in support of developmentally grounded redesigns of juvenile probation.